Investigation of ego and task orientation among international wrestling referees - Barbas, I.; Bebetsos, E.; Christos, K.; Curby, D.; Mirzaei, B. (Physical Education of Students, 2016)
Aim: study was to investigate any possible effect(s) of experiences from active membership and participation in task or ego orientations among referees in the sport of wrestling. Material: The sample consisted of 213 international referees from 30 countries (Greece, Turkey, Bulgaria, France, Italy, Germany, Sweden, Finland, Switzerland, Russia, Poland, Hungary, U.S.A, Ukraine, Armenia, Azerbaijan, Iran, Japan, Korea, Mongolia, Kazakhstan, Egypt, Canada, Georgia, Croatia, Uzbekistan, Norway, Cuba, Belarus, & Tunisia). Their age ranged from 26 to 60 yrs. old ( M =43, SD =8.6). During the procedure, the participants were asked to fill a specific questionnaire, the «Task and Ego Orientation in Sport Questionnaire» (Duda & Nicholls, 1992). Results: Results showed that the referees from elite wrestling level` countries (Russia, Azerbaijan, Iran, Turkey, Georgia, Armenia, Bulgaria, Ukraine, U.S.A., Korea, Japan, Kazakhstan, & Cuba) are more task oriented than those from the non-elite wrestling level` countries. Researchers believe that this occurred because referees from non-elite wrestling level` countries might have less game-sport experience and more specifically in high level games. At the same time, the Olympic experience referees were more task oriented than the non-Olympic experienced. Conclusion: Referee`s decisions are an important issue in the sport milieu. The investigations in decision-making by referees and factors that affect it are rather scarce and research should focus on such topics. Improvement of decision-making by referees, would lead to safer and better performance. Thus, better understanding of referees` behavior, through identification and operationalization of the factors affecting it, might lead to more effective selection, training and performance.